Edith Banfield Jackson papers - Jackson, Edith Banfield, 1895-1977.
ALS (1946 January 13) to Jackson from Otto Fenichel and ALS with attached curriculum vitae (1939 May 17) to Jackson from Maximilian Steiner.
Physician.
In German and English.
Forms part of: Sigmund Freud collection.
Keywords: Fenichel, Otto -- Correspondence; Steiner, Maximilian, -- 1874-1942 -- Correspondence; Physicians